2017
DOI: 10.1515/bjmg-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immunohistochemical characteristics of complete hydatidiform moles

Abstract: Molar pregnancy is a gestational trophoblastic disease that belongs to the category of precancerous lesions. On the other end of the spectrum are gestational trophoblastic neoplasms such as invasive mole, choriocarcinoma, placental site trophoblastic tumor and epithelioid trophoblastic tumor, which are considered malignant tumors. Based on defined histopathological criteria, molar pregnancy is divided into partial and complete hydatidiform mole. Especially in the case of early complete mole, the diagnosis can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The pathologic criteria must be strict in the diagnosis of ectopic molars, as some studies have found that there may be an overdiagnosis of ectopic molar pregnancy [1,13]. However, diagnosis can be a challenge to the pathologist since the differences in hydropic abortions and molar pregnancy can be minimal, especially in early miscarriages [14], add to this, evaluation of the specimen depends on the experience of the examiner and might be highly subjective [15]. On the other hand immunohistochemical analysis using antibodies like p57 can distinguish between hydatidiform mole with its different types and hydropic miscarriage [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathologic criteria must be strict in the diagnosis of ectopic molars, as some studies have found that there may be an overdiagnosis of ectopic molar pregnancy [1,13]. However, diagnosis can be a challenge to the pathologist since the differences in hydropic abortions and molar pregnancy can be minimal, especially in early miscarriages [14], add to this, evaluation of the specimen depends on the experience of the examiner and might be highly subjective [15]. On the other hand immunohistochemical analysis using antibodies like p57 can distinguish between hydatidiform mole with its different types and hydropic miscarriage [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, diagnosis can be a challenge to the pathologist since the differences in hydropic abortions and molar pregnancy can be minimal, especially in early miscarriages [14], add to this, evaluation of the specimen depends on the experience of the examiner and might be highly subjective [15]. On the other hand immunohistochemical analysis using antibodies like p57 can distinguish between hydatidiform mole with its different types and hydropic miscarriage [14]. When available, DNA flow cytometric analysis to determine ploidy helps to differentiate between complete mole and partial mole [2].…”
Section: Discussionmentioning
confidence: 99%